2021
DOI: 10.3389/fcell.2021.732415
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between microRNAs and the Pathological Features of Secondary Lymphedema

Abstract: Secondary lymphedema is characterized by lymphatic fluid retention and subsequent tissue swelling in one or both limbs that can lead to decreased quality of life. It often arises after loss, obstruction, or blockage of lymphatic vessels due to multifactorial modalities, such as lymphatic insults after surgery, immune system dysfunction, deposition of fat that compresses the lymphatic capillaries, fibrosis, and inflammation. Although secondary lymphedema is often associated with breast cancer, the condition can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 119 publications
(156 reference statements)
0
2
0
Order By: Relevance
“…P. gingivalis LPS induces the overexpression of miRNAs 146-a and -b in gingival fibroblasts, subsequently enhancing the secretion of TNF-α, IL-6, and IL-1β. [ 43 , 44 , 45 ] Furthermore, miRNA-155 promotes the formation of atherosclerotic plaques, and its downregulation following NSPT may offer benefits in reducing CVD risk in PD and DM patients. [ 22 , 40 ]…”
Section: Discussionmentioning
confidence: 99%
“…P. gingivalis LPS induces the overexpression of miRNAs 146-a and -b in gingival fibroblasts, subsequently enhancing the secretion of TNF-α, IL-6, and IL-1β. [ 43 , 44 , 45 ] Furthermore, miRNA-155 promotes the formation of atherosclerotic plaques, and its downregulation following NSPT may offer benefits in reducing CVD risk in PD and DM patients. [ 22 , 40 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that alterations in regulatory microRNA (miRNA) expression may mediate the pathophysiologic features of various disease states, such as dermal inflammation, fibrosis, and immune dysregulation [ 98 ]. Expression of miR-1236 in LECs is associated with the inhibition of lymphangiogenesis via VEGFR3, Akt, and ERK downregulation [ 99 ] ( Figure 2 a).…”
Section: Lymphedema and Other Lymphatic Anomaliesmentioning
confidence: 99%
“…Due to their functionally active properties and stability within vesicles, miRNAs have been extensively studied as potential biomarkers in various diseases such as Alzheimer’s [ 8 , 9 ], cancers [ 10 ], and cardiovascular diseases [ 11 , 12 ]. To our knowledge, an understanding of the role of miRNAs in secondary lymphedema remains to be explored, but evidence from related pathological conditions indicates their potential involvement [ 13 ]. For instance, miR-29 has been found to be a negative regulator of skin fibrosis, one of the hallmarks of lymphedema.…”
Section: Introductionmentioning
confidence: 99%